Impact of Firms’ Innovation and Environmental, Social, and Governance (ESG) Score on Financial Performance: A Study of Telecommunications and Information Technology Companies Listed on APEC Member Countries’ Stock Exchanges in the Period of 2018-2022 - Apriliani, Navira Putri; Baskoro, Rahmat Aryo (UI Scholars Hub, 2025)
The telecommunications and information technology sectors significantly drive economic growth through continuous innovation. This study investigates how Innovation and Environmental, Social, and Governance (ESG) metrics affect the financial performance of 80 telecommunications firms listed on stock exchanges in APEC member nations from 2018 to 2022. Innovation is evaluated based on research and development expenditures, whereas financial performance is determined by examining revenue and Tobin’s Q. Employing Ordinary Least Squares (OLS) and Two-Stage Least Squares (2SLS) regression methods, the findings reveal that innovation positively influences ESG scores, notably improving governance aspects. ESG scores positively impact revenue but negatively affect Tobin’s Q. Furthermore, the environmental and social scores of ESG contribute positively to revenue while showing significant and negative effects on Tobin’s Q, whereas the governance pillar demonstrates no significant influence. These findings emphasize the need for customized ESG rating approaches and reveal the varied financial impacts of ESG practices in the telecommunications and information technology industry.